(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2022)
In this article I report on the current and emerging practices of UPLOrc (University of Pretoria Laptop Orchestra), a networked live coding laptop orchestra based in Southern Africa. Since its establishment in 2019, the ensemble has performed live coded network music using the TidalCycles live coding environment at various conferences and live streamed events. The development of these practices is owed to, among other aspects, the fieldwork experience I obtained with the trans-continental network ensemble SuperContinent. I describe how this knowledge has been implemented into the activities of UPLOrc, alongside some of our own emerging practices. Particular problems that emerged during the performance preparation process is also highlighted, as well as the strategies that could be implemented to address some of these problems.